Physical Activity Protects Against the Negative Impact of Coronavirus Fear on Adolescent Mental Health and Well-Being During the COVID-19 Pandemic - Wright, Laura J.; Williams, Sarah E.; Veldhuijzen van Zanten, Jet J. C. S. (Frontiers in Psychology, 2021)
Background: The severity of the Coronavirus pandemic has led to lockdowns in different countries to reduce the spread of the infection. These lockdown restrictions are likely to be detrimental to mental health and wellbeing in adolescents. Physical activity can be beneficial for mental health and wellbeing, however, research has yet to examine associations between adolescent physical activity and mental health and wellbeing during lockdown. Purpose: Examine the effects of adolescent perceived Coronavirus prevalence and fear on mental health and wellbeing and investigate the extent to which physical activity can be a protective factor against these concerns. Methods: During UK lockdown restrictions, 165 participants (100 female, aged 13-19) completed an online questionnaire assessing perceived Coronavirus prevalence and fear, physical activity, and indicators of mental health and wellbeing (stress, anxiety, depression, fatigue, vitality, and perceived health). Results: Regression analyses indicated that in general, while Coronavirus fear was a negative predictor, physical activity was a positive and stronger predictor of enhanced mental health and wellbeing outcomes. Conclusions: Findings suggest that physical activity during the Coronavirus pandemic can counteract the negative effects of Coronavirus fear on adolescent mental health and wellbeing. Therefore, physical activity should be promoted during lockdown to support good mental health and wellbeing